(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Financial statements are important information for decision makers, because they contain the financial position, performance and changes in the company’s financial position. However, determining the performance of a company can be used in various ways and functions to get benefits as information in determining the direction of company policy. The objectives of this research are to formulate the design of earning management formulations and models, measure intellectual capital, and the level of efficiency in the corporate services sector in Indonesia. Furthermore, testing is carried out to make a prediction model about the consequences of earning management actions, intellectual capital, and efficiency ratio on Company Performance in Indonesia. The chosen research subjects are the Health services sub-sector company and the Restaurant, Hotel and Tourism sub-sector operating in Indonesia from 2013 to 2018. The data analysis method used is Path Analysis. The results showed that only earnings management, intellectual capital from VACA, and efficiency of the SFA ratio only affect the Company’s performance while the intellectual capital from VAHU and STVA has no effect on company performance. The implication of this research is that service companies in Indonesia still apply earnings management in conducting their business, while in terms of intellectual capital, the role is only the company’s ability to utilize its capital